Analisa Kemampuan Mahasiswa dalam Menggunakan Cohesive Devices dalam Menulis Teks Analitikal Eksposisi - Aprida irma yana; Lollo Rosa Lubis (Institut Pendidikan Tapanuli Selatan, 2018)
This research aims to explain the students’ writing ability in term of cohesive writing and to analyze the factor that causes students’ problems in using cohesive devices in writing analytical expository text. This research is a mixed method research purpose to build on the synergy and strength that exist between quantitative and qualitative research methods to understand a phenomenon. The data were the fourth semester students of English department of Institut Pendidikan Tapanuli Selatan. The sample were consisting of 40 students. The finding shows that the quality of students’ writing was in the level of low category. They have problems in using cohesive devices. The problems are related to the use of reference, substitution, ellipsis, conjunction and lexical cohesion. The reason of the problems in using cohesive devices in writing is based on linguistic, pragmatic, cognitive and cultural factor. Four of them give influence that causes the lack cohesive writing. Therefore, an intensive attention should be given by the lecture to facilitate the students to practice writing in the classroom and do peer correction.